Application of Science Media for Science Communication in Postgraduate Course to Elicit Emancipation - Abdul Rahman, Nor Farahwahidah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study reports on redesigning learning outcomes in terms of postgraduates’ communication skills through science media communication with the aim for interactive teaching and learning. Communication in science education entails the image of science known as scientific epistemology. Therefore, the inclusion for learning about the philosophy of science among postgraduate students must not be limited to understanding the descriptive tenet of the philosophy. The initial work for this study attempts to assess whether learning about the philosophy of science dictates reflexivity and emancipation. Previous studies have not reached a consensus on how the impact of transformation can be created and recreated for others. Therefore, this study focuses on leveraging science media communication to foster conformity between oneself and others. Analysis was performed on ten postgraduate students’ reports, writings, and portfolios obtained throughout the semesters. The analysis aims to critically discuss the proposed solution for the paradigm shift in teaching practice, with a specific focus on the course design outcomes. Using critical discourse analysis (CDA), the analysis identified liminal phases due to bearer as a professional among the respondents that habitually liberated through the five stages of transformation designed for this course. The following four liminal phases were interpreted from the students’ reflexivity: identify negotiation, setup condition, a masking mechanism, and formation of oneself and others. Such points to the conclusion that placing students as the protagonist during the transformation process when learning the philosophy of science would expand their self-realization on the role of scientific epistemology in science education.